2014
DOI: 10.1111/tpj.12630
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation maintenance consolidates RNA‐directed DNA methylation and transcriptional gene silencing over generations in Arabidopsis thaliana

Abstract: SUMMARYIn plants, 24 nucleotide short interfering RNAs serve as a signal to direct cytosine methylation at homologous DNA regions in the nucleus. If the targeted DNA has promoter function, this RNA-directed DNA methylation may result in transcriptional gene silencing. In a genetic screen for factors involved in RNA-directed transcriptional silencing of a ProNOS-NPTII reporter transgene in Arabidopsis thaliana, we captured alleles of DOMAINS REARRANGED METHYLTRANSFERASE 2, the gene encoding the DNA methyltransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 76 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…The results of analysis of the DNA methylation of specific genes showed that the degree of DNA methylation of the promoter −109 to −279 bp region in the flanking region of the phenylalanine ammonia-lyase2 gene of L. maackii was higher than that of L. maackii, and the degree of DNA methylation of the CG site was significantly different between the two [28]. In the present study, we conducted DNA methylation analysis of the key enzymes [29,30], so were regarded as DNA methylation nonspecific sites of gene promoters. The SS cytosine at −558 and cytosines at positions −684 and −847 of the SE gene were specific sites involved in the regulation of gene expression that need further research.…”
Section: Discussionmentioning
confidence: 72%
“…The results of analysis of the DNA methylation of specific genes showed that the degree of DNA methylation of the promoter −109 to −279 bp region in the flanking region of the phenylalanine ammonia-lyase2 gene of L. maackii was higher than that of L. maackii, and the degree of DNA methylation of the CG site was significantly different between the two [28]. In the present study, we conducted DNA methylation analysis of the key enzymes [29,30], so were regarded as DNA methylation nonspecific sites of gene promoters. The SS cytosine at −558 and cytosines at positions −684 and −847 of the SE gene were specific sites involved in the regulation of gene expression that need further research.…”
Section: Discussionmentioning
confidence: 72%
“…The inheritance of accumulated epimutations showed epigenetic inheritance, which was not due to underlying genetic variation (genetic inheritance)27, as all analyses were based on samples from a common ancestor and genetic variation was almost completely absent. In a similar study in A. thaliana , RNA-directed de novo DNA methylation in CG dinucleotides was stably transmitted to offspring for at least three generations8.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have revealed that heritable epimutations play important roles in plant growth and development7. In Arabidopsis thaliana , RNA-directed de novo DNA methylation of CG dinucleotides is stably inherited, and in offspring, this methylation affects the transcription of the target gene8. Moreover, transgenerational epimutations have critical functions in the adaptations of plants to their changing environments because epimutation states can be modified by environmental factors and are reversible910.…”
mentioning
confidence: 99%
“…Intriguingly, the transcription and transposition of a substantial proportion of TEs are extensively controlled by endogenous or exogenous siRNAs through an RNA‐directed DNA methylation (RdDM) pathway (Xie et al ., ; Kuhlmann et al ., ; Marré et al ., ; Houri‐Zeevi and Rechavi, ). Furthermore, double‐stranded RNA (dsRNA), the precursor of siRNA, can be derived from the complementary inverted terminal repeats in DNA transposons (Levin and Moran, ).…”
Section: Introductionmentioning
confidence: 99%